1998
DOI: 10.1095/biolreprod59.5.1171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photoperiod and Age on Secretory Patterns of Luteinizing Hormone and Testosterone and Semen Production in Male Domestic Turkeys1

Abstract: The objective of this study was to determine effects of photoperiod and age on the circulating concentrations of LH, testosterone (T), thyroxine (T4), and semen production in male turkeys. Male turkeys from 10 or 12 wk of age were maintained under either a long-day (LD) photoperiod of 16L:8D up to 35 wk (LL), or a short-day (SD) photoperiod of 6L:18D to 29 wk and then an LD photoperiod of 16L:8D up to 35 wk of age (SL). Plasma concentrations of both LH and T increased by 17 or 18 wk of age under both photoperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
3
11
0
1
Order By: Relevance
“…Previous studies using commercial breeder turkeys revealed a high degree of sensitivity to photoperiod for TW [10,11], semen output [18], and circulating LH and testosterone concentrations [6][7][8][9]. The present results confirmed previous observations [10,11] that prepubertal male turkeys maintained under constant long days are precocious semen producers (26-29 wk) In .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Previous studies using commercial breeder turkeys revealed a high degree of sensitivity to photoperiod for TW [10,11], semen output [18], and circulating LH and testosterone concentrations [6][7][8][9]. The present results confirmed previous observations [10,11] that prepubertal male turkeys maintained under constant long days are precocious semen producers (26-29 wk) In .…”
Section: Discussionsupporting
confidence: 90%
“…We suggest that this cannot be attributed to juvenile photorefractoriness that is expressed in wild birds not having reached full body development [19]. Our study also confirmed previous observations that a short, reputedly non-stimulatory photoperiod may induce precocious sexual maturity (26-29 wk) in a minority (here about 30%) of the experimental population [9]. Hypothetically, such turkeys possess the genetic capacity to reach a functionally reproductive state when subjected to a ''normally'' non-stimulatory environment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The testosterone value of male turkeys ranged from 0.4 to 2.0ng/cm-3 until sexual maturity and reached 4.0ng/cm-3 at 29 weeks of age when semen production increased (Yang et al, (1998). Similarly, Blaszczyk et al, (2006) reported a value range of 4.39ng/cm-3 of plasma testosterone in male quail but at 56 days old with ranges of 1.39-4.39ng/cm-3 (40-66 days of age) for male and 0.23-1.27ng/cm-3 for female over the same period with peak concentration of 1.27ng/cm-3 on the 60 th day.…”
Section: Introductionmentioning
confidence: 99%